MANAGEMENT OF LEARNING IN MAWADDAH ISLAMIC KINDERGARTEN AND SABILAL MUHTADIN INTEGRATED ISLAMIC KINDERGARTEN - Rahmah, Ajizatur; Suriansyah, Ahmad; Wahdini, Erny (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The purpose of this research is to describe the planning, organization, implementation, and evaluation of learning in kindergarten students. It is a qualitative and multi-site study with data obtained from Mawaddah and Sabilal Muhtadin Integrated Islamic Kindergarten. Research results show that planning Weekly Learning Implementation Plan and Daily Learning Implementation Plan with an academic calendar organized following the Education Office, based on teacher expertise and distributing Standard Operating Procedures. Furthermore, students were grouped according to their habits, age, observation results, and the stage of development for one year. At the implementation stage, teachers were supervised, with learning taught according to the daily learning implementation plan, to meet children's needs and following the themes raised by the daily learning implementation plan. Evaluating the results of child development, with questions asked on the right learning material taught every month, with follow-up improvement to deal with children with special.